The Representation of Mexican-Americans’ Life Stages through the Models in Luis Valdez’s Los Vendidos - Christianto, Adi Prasatya; Widyastuti, Dewi (Universitas Sanata Dharma, 2014)
Literature and history are interrelated. Literature does not only serve for entertainment but it also serves as a historical record of certain society in certain period. Through literature, many history and events can be examined. This is particularly why Los Vendidos becomes an interesting example. It examines Mexican-Americans’ history through its satirical element. The model characters in the play describe not only distinctive characteristics but also specific perception and condition of Mexican-Americans’ life in different periods, or stages. Each model represents the reality of Mexican-Americans’ history. Thus, at the end, this research will not only evaluated Mexican-Americans’ history or discrimination, but it also examine the whole life, the culture and the ideology of Mexican-Americans.Keywords: Mexican-Americans’ history, models, stages